Spectral evolution and stimulated Brillouin scattering suppression in phase-modulated fiber amplifier. (11th April 2018) - Chu, Qiuhui; Lin, Honghuan; Tang, Chuanxiang; Jing, Feng; Tang, Xuan
Abstract: The model combining power balance equations, coupling amplitude equations and stimulated Brillouin scattering (SBS) equation is established to simulate the spectrum evolution and SBS threshold in the amplifier stage. Four typical phase modulation seeds are employed to calculate the SBS spectrum evolution in fiber amplifier. The spectrum evolution results show that the top-hat shaped spectrum seed is optimal to suppress the SBS effect and scale the SBS threshold. The SBS threshold is studied in co-pumped and counter-pumped amplifiers. Simulation results show that counter-pumped amplifier is capable of generating about 2.5 times more output than co-pumped amplifier. The results provide theoretical basis on the design and experiment of continuous wave high power narrow linewidth fiber laser.